Analysis of Policy Based Routing (PBR) and Failover in Dual-WAN Networks - Daryan Pratama Alifi; Ichwan Nul Ichsan (Institut Teknologi Dirgantara Adisutjipto, 2026)
Reliance on stable and high-speed internet connectivity is crucial for modern business operations. A failure in a single internet link often leads to significant disruptions in productivity. This study designs and implements a Dual-WAN network architecture utilizing Policy-Based Routing (PBR) combined with an automated failover mechanism on a MikroTik router. Unlike prior studies that primarily employ the Per-Connection Classifier (PCC) Load Balancing method to maximize bandwidth aggregation, this research prioritizes session integrity to minimize disruptions in sensitive applications. To validate the proposed method, a comparative analysis was performed against the conventional PCC method. The results indicate that while PCC yields a higher theoretical aggregated throughput (468.5 Mbps), it suffers from a high session drop rate in secure connections. In contrast, the proposed PBR implementation demonstrates superior connection stability with a maximum throughput of 344.25 Mbps on the primary link, alongside a responsive failover mechanism achieving a recovery latency of under 1000 ms with minimal packet loss (1–2 packets). This study concludes that the PBR architecture provides a more reliable solution compared to standard load balancing for Small Office Home Office (SOHO) and SME environments requiring high availability.